Hydrocode simulations of few Lutetia craters - Cremonese, G.; Martellato, E.; Marzari, F.; Kuehrt, E.; Scholten, Frank; Preusker, Frank; Wunnemann, K.; Borin, P.; Massironi, Matteo; Simioni, E.; IP, W.H. (2011)
The flyby of the Main Belt asteroid Lutetia by the Rosetta spacecraft allows the camera OSIRIS to obtain very good images of about half body at the maximum resolution of 60 m per pixel. Moreover, the data obtained by the Rosetta instruments include the asteroid density of about (3.4 ± 0.3) g/cm3. Many impact craters have been observed on the surface of Lutetia. The largest among them is called Massilia and has a diameter of about 55 km. Relative to the size of Lutetia (the longest axis is approximately 126 km) the crater represents one of the dominating features on the surface. Whether the impact that formed the crater affected the entire asteroid can only be estimated from numerical analysis of hydrocode modeling of the impact processes. The results of a suite of iSALE simulations are compared with the crater profile derived from the Digital Terrain Model of the observed surface. The final hydrocode simulations allowed to determine the impactor size having a diameter of 7.5 km which suggests a primordial origin of Lutetia due to the low probability for such an impact event. A second interesting impact structure has been identified nearby Massilia within the North Pole Crater Cluster. This crater, having a diameter of 24 km and lying over the other craters of the North Pole Crater Cluster, seems to be the youngest largest structure of Lutetia.- The numerical simulations of this feature constrain the impactor to be of 3.8 km in diameter, assuming the same material properties for target and impactor as in the model of the formation of Massilia.